(untitled) (Academic Journal of Internal Affairs, 2022)
Aim: Nowadays in our fast-moving world, road transport drivers tend to perform other activities that are important to them and require considerable mental capacity, such as communicating oral or written on technical tools, which are completely unrelated to driving. Distraction activities are generally prohibited by the legal system because of their risk-increasing character, but not entirely. The use of a hand-held mobile phone is prohibited, but the various headsets are not. The aim of this study is to investigate how safe it is to drive and talk on the mobile phone at the same time, and how it affects the driver’s attention. Methodology: Our study presents previous research about the relationship between phone use while driving and the occurrence of traffic accidents. The increasing number and range of services offered by on-board computers in vehicles, which are increasingly advanced, raises the question: Can the technological innovations reduce the frequency of road traffic accidents? Findings: From a road safety perspective, the most important negative effects of distraction and phone use are the cognitive impairments, which has been supported by a number of psychological studies. Although a driver may be capable of performing two activities, divided attention while driving can have serious consequences. In fact, there is evidence that talking on a mobile phone has a disturbing effect on the driver even after the conversation has ended. The outcome of a traffic situation also depends on the driver’s situational awareness. Value: Our findings provide a basis for pedagogical work in driver training and for the police’s activities in controlling and sanctioning infringements. Besides talking on the phone, future research will also be able to prove how dangerous the other used phone apps are to the car drivers while they are driving.